Features of metropolitan area governance models - Yu. V. Pavlov; G. A. Khmeleva (Управление)
The article develops a methodological basis for choosing the optimal model for managing the agglomeration of settlements. The existing agglomeration problems and the need to accelerate growth due to the agglomeration effect form a challenge to the agglomeration governance system. For an adequate response it is important to understand the capabilities of governance models. These capabilities can be expressed through the description of the features of the models.For a large-scale description of the features of models, it is necessary to form groups of features, characterize each feature, compare the models according to the degree of its manifestation, and, if possible, explain the reason for the differences. The article investigates research papers within the framework of the theory of municipal reformers, the theory of public choice, in particular on the issues of centralization / decentralization of municipalities, intermunicipal cooperation, the efficiency of the economy of the public sector. The authors used general scientific methods of analysis, synthesis, grouping, comparison.The revealed features make it possible to assess the governance model in terms of what the agglomeration will receive from its implementation. All features are combined into five groups: economic, social, administrative efficiency, democratization, stability. The study revealed 29 features, presented their explanation and degree of development, depending on the type of governance model.As a result of the study, the possibilities for justifying the feasibility of introducing models have increased. The authors represented scientific novelty by a more complete list of the features of models, a more detailed presentation of them, the approach of presenting information “from features”, a convenient grouping that allows you to use the characteristic to assess the effectiveness of the activities of government authorities. The study can be useful for civil servants in charge of agglomeration processes.